2010
DOI: 10.1001/archpediatrics.2009.240
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Effects of Prenatal and Infancy Nurse Home Visitation on the Life Course of Youths

Abstract: Objective:To examine the effect of prenatal and infancy nurse home visitation on the life course development of 19-year-old youths whose mothers participated in the program.Design: Randomized trial.Setting: Semirural community in New York.Participants: Three hundred ten youths from the 400 families enrolled in the Elmira Nurse-Family Partnership program.Intervention: Families received a mean of 9 home visits (range, 0-16) during pregnancy and 23 (range, 0-59) from birth through the child's second birthday. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(204 citation statements)
references
References 29 publications
4
197
0
3
Order By: Relevance
“…In long-term panels, young children with better language, cognitive, motor, and socio-emotional development have better outcomes in adulthood (Case and Paxson 2008;Currie and Thomas 2001;Moffitt et al 2011). Plausibly exogenous improvements in maternal education (Carneiro et al 2013), early nutrition (Hoddinott et al 2008;Maluccio et al 2009), the quality of the home environment (Eckenrode et al 2010;Gertler et al 2014;Olds et al 1998), preschool attendance (Berlinski et al 2008;Campbell et al 2002Campbell et al , 2014Heckman et al 2010), and kindergarten classroom quality (Chetty et al 2011) have been shown to result in higher school achievement, better health status, lower levels of criminal behavior, and better labor market outcomes in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…In long-term panels, young children with better language, cognitive, motor, and socio-emotional development have better outcomes in adulthood (Case and Paxson 2008;Currie and Thomas 2001;Moffitt et al 2011). Plausibly exogenous improvements in maternal education (Carneiro et al 2013), early nutrition (Hoddinott et al 2008;Maluccio et al 2009), the quality of the home environment (Eckenrode et al 2010;Gertler et al 2014;Olds et al 1998), preschool attendance (Berlinski et al 2008;Campbell et al 2002Campbell et al , 2014Heckman et al 2010), and kindergarten classroom quality (Chetty et al 2011) have been shown to result in higher school achievement, better health status, lower levels of criminal behavior, and better labor market outcomes in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…How do we use epigenetic concepts to design interventions? Prevention research has shown that early life preventive interventions can have long-lasting effects on the children into adulthood [37][38][39][40]. Could epigenetic markers be used to follow up these interventions?…”
Section: Summary and Prospectivementioning
confidence: 99%
“…These visitations also have been associated with reduced risk of serious antisocial behavior and substance abuse by adolescent offspring followed up during the first 15 years of life. [98][99][100][101] Multidimensional family and peer support with positive role models and concrete examples of how to overcome challenges has also been shown to help teenagers initiate and continue breastfeeding. 102 …”
Section: Peer Group and Role Model Programsmentioning
confidence: 99%